2017
DOI: 10.1080/0284186x.2016.1266081
|View full text |Cite
|
Sign up to set email alerts
|

Promoting a culture of prehabilitation for the surgical cancer patient

Abstract: Background: Traditional rehabilitative approaches to perioperative cancer care have focused on the postoperative period to facilitate the return to presurgical baseline conditions. However, there is some realization that the preoperative period can be a very effective time for intervention as the patients are more amenable to target their physiological condition to prepare to overcome the metabolic cost of the surgical stress. Methods: We undertook a narrative review of the current literature on surgical preha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
98
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(104 citation statements)
references
References 41 publications
1
98
0
5
Order By: Relevance
“…For example, evidence‐based multimodal prehabilitation programs have demonstrated some efficacy in contributing to improved patient outcomes within ERAS programs . Prehabilitation offers individualized nutrition (eg, counseling and supplemental protein, n‐3 fatty acids), function (exercise program), and anxiety reduction to promote metabolic preparation and optimization of health status beginning preoperatively and extending into recovery . AHS is working toward a standardized perioperative nutrition care pathway within the ERAS paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…For example, evidence‐based multimodal prehabilitation programs have demonstrated some efficacy in contributing to improved patient outcomes within ERAS programs . Prehabilitation offers individualized nutrition (eg, counseling and supplemental protein, n‐3 fatty acids), function (exercise program), and anxiety reduction to promote metabolic preparation and optimization of health status beginning preoperatively and extending into recovery . AHS is working toward a standardized perioperative nutrition care pathway within the ERAS paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…We found that this significantly improves the patient's preparation for surgery and encourages them to take responsibility for their recovery. Studies have shown that an exercise program prior to surgery can improve function after surgery (12,13). This has helped patients to recover faster with fewer complications.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] There has also been emerging research in prehabilitation, for multimodal programs involving exercise, nutrition, smoking cessation, and psychologic support. 13,14 Nevertheless, it is unclear if this interest has translated into the clinical domain. This evidence-to-practice gap in healthcare is typically 17 years 15 ; implementation science in the field of perioperative care is only an emerging field.…”
Section: Résumémentioning
confidence: 99%